AVOID Game: Media to Foster Self-Awareness for Children Aged 5-6 Years Old - Shalma Risanangta; Avanti Vera Risti Pramudyani; Riana Mashar; Febritesna Nuraini (Universitas Pendidikan Ganesha, 2026)
Children who have limited ability to recognize their own identity and social environment are more vulnerable to various dangerous situations, including the risk of abduction. This condition highlights the importance of developing self-awareness from an early age as part of personal safety education. This study aims to analyze the use of the AVOID Game as a learning medium to foster self-awareness related to personal safety among children aged 5–6 years. The study employed a qualitative method with a case study approach involving two informants and two participants. Data were collected through interviews, observations, and documentation using interview guidelines, observation sheets, and activity documentation. Data trustworthiness was ensured through technique triangulation, while data analysis was conducted through the stages of data collection, data description, data reduction, data categorization, and data construction. The findings indicate that the AVOID Game supports the development of children’s self-awareness through self-identity recognition, the ability to distinguish between safe and unsafe situations, the recognition of dangerous situations, the development of responsibility for personal safety, and the ability to make appropriate decisions. Levels 1 and 2 focus on introducing children to their identity and the people around them, while Level 3 trains children to recognize risks and determine appropriate responses in dangerous situations. The study concludes that interactive games have the potential to serve as effective learning media for strengthening the elements of self-identity as well as religious and moral values in early childhood education. The implication of this study is the utilization of educational games as an alternative learning medium to enhance children’s self-awareness and personal safety from an early age.